A new approach to the room impulse response simulation - Łopacz, H.; Marczuk, R. (Archives of Acoustics, 2004)
The most important problem of room acoustics is the evaluation of the acoustic quality of projected and modernized rooms. To this end it is necessary to work out a calculating impulse response algorithm for a digital room model. The virtual rooms impulse response manners of modeling are described in the article. The impulse response synthetic models have been evaluated on the basis of selected numerical factors and a simple auditory test. Thanks to the impulse response calculation it is possible to evaluate the subjective and objective room acoustic properties and hence to run the room simulation tests (the sound sources configuration, the room planning) in order to reach optimal solutions, which meet a given criterion. The problems described are related to the ’’virtual sound space’’ concept. Intuitively, we mean by this a sound reality model, which enables, on the basis of the model and measurement data, an audio impressions simulation of the existing and being under projection acoustic systems. A basic process, which enables the sound reception, is the test signal and the impulse response convolution.